Light‐Harvesting Nanoparticle Probes for FRET‐Based Detection of Oligonucleotides with Single‐Molecule Sensitivity. (27th February 2020) - Melnychuk, Nina; Egloff, Sylvie; Runser, Anne; Reisch, Andreas; Klymchenko, Andrey S.
Abstract: Controlling the emission of bright luminescent nanoparticles by a single molecular recognition event remains a challenge in the design of ultrasensitive probes for biomolecules. Herein, we developed 20‐nm light‐harvesting nanoantenna particles, built of a tailor‐made hydrophobic charged polymer poly(ethyl methacrylate‐co‐methacrylic acid), encapsulating circa 1000 strongly coupled and highly emissive rhodamine dyes with their bulky counterion. Being 87‐fold brighter than quantum dots QDots 605 in single‐particle microscopy (with 550‐nm excitation), these DNA‐functionalized nanoparticles exhibit over 50 % total FRET efficiency to a single hybridized FRET acceptor, a highly photostable dye (ATTO665), leading to circa 250‐fold signal amplification. The obtained FRET nanoprobes enable single‐molecule detection of short DNA and RNA sequences, encoding a cancer marker (survivin), and imaging single hybridization events by an epi‐fluorescence microscope with ultralow excitation irradiance close to that of ambient sunlight. Abstract : Lichtabsorbierende Nanosonden auf Basis polymerer Nanopartikeln, die rund 1000 stark gekoppelte und hoch emittierende Farbstoffe verkapseln, liefern eine FRET‐Effizienz von über 50 % an einen einzelnen Akzeptor an der DNA‐funktionalisierten Oberflächen. Dieses Nanomaterial ermöglicht den Nachweis einzelner DNA/RNA‐Kopien mit einem einfachen Epifluoreszenzmikroskop mit niedriger Anregungsleistung nahe der von Umgebungslicht.